1992
DOI: 10.1007/bf01270576
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial fatty acid oxidation during ischemia and reperfusion

Abstract: Inhibition of fatty acid oxidation is an early event in myocardial ischemia that most likely contributes to tissue injury by the accumulation of potentially toxic intermediates such as acylCoA and acylcarnitine. After reperfusion both myocardial oxygen consumption and fatty acid oxidation may rapidly recover to preischemic levels, even when contractile function remains depressed. The mechanisms underlying the apparent dissociation between contractile function and oxidative metabolism early during reperfusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 52 publications
(75 reference statements)
2
26
0
2
Order By: Relevance
“…Previous studies have shown that FAs released by intracellular TG hydrolysis contribute significantly to the generation of ATP necessary for contractile function (2,34,39), suggesting that TG hydrolysis plays a critical role in regulating cardiac function. In agreement with this finding, dysregulation of myocardial TG metabolism and either increased or reduced TG content have been associated with cardiac dysfunction and/or heart failure induced by obesity, diabetes, aging, ischemia, and hemodynamic pressure overload (3,5,8,22,26,(31)(32)(33)(34). Moreover, a clear correlation between increased myocardial TG content and decreased cardiac function has been established in rodents and humans (7,12,22,24), supporting the concept that excessive TG accumulation in the heart is detrimental.…”
supporting
confidence: 63%
“…Previous studies have shown that FAs released by intracellular TG hydrolysis contribute significantly to the generation of ATP necessary for contractile function (2,34,39), suggesting that TG hydrolysis plays a critical role in regulating cardiac function. In agreement with this finding, dysregulation of myocardial TG metabolism and either increased or reduced TG content have been associated with cardiac dysfunction and/or heart failure induced by obesity, diabetes, aging, ischemia, and hemodynamic pressure overload (3,5,8,22,26,(31)(32)(33)(34). Moreover, a clear correlation between increased myocardial TG content and decreased cardiac function has been established in rodents and humans (7,12,22,24), supporting the concept that excessive TG accumulation in the heart is detrimental.…”
supporting
confidence: 63%
“…11,12 Multiple complementary mechanisms may contribute to GIK-related myocardial protection: (1) suppression of lipolysis, resulting in a reduction of circulating levels of free fatty acids available for cardiac metabolism [13][14][15][16] ; (2) an increase in insulin-related glucose flux and myocardial oxygen efficiency, increasing cardiac energy provision (ie, glycolytic ATP), 17 which may augment myocardial glycogen levels 18 -20 and may mitigate the consequences of low myocardial pH 21 ; (3) beneficial augmentation of tricarboxylic acid intermediates (anaplerosis) 22 ; and (4) through the pleiotropic signaling properties of insulin, including its antiapoptotic properties acting via phosphatidylinositol 3-kinase (PI3K), it may directly reduce myocardial injury. 23 Activation of a cascade of what have been called reperfusion injury salvage kinases such as PI3K/protein kinase B (Akt) and AMP-activated protein kinase (AMPK), which have an established role in insulin signaling, 24 may also have a role in cardioprotection.…”
Section: Editorial See P 129 Clinical Perspective On P 177mentioning
confidence: 99%
“…Although the energetics during ischemia are extremely important, it has been shown that after ischemia, fatty acid oxidation also dominates as a source of energy by the heart. 4,5,15,19,20 Although we did not measure fatty acid oxidation rates during reperfusion in this study, it has already been shown that during reperfusion of ischemic hearts, there is a close relationship between fatty acid oxidation and glucose oxidation, with high rates of fatty acid oxidation resulting in stoichiometric decreases in glucose oxidation. 15 This results in a continued decrease in cardiac efficiency during the critical period of reperfusion.…”
mentioning
confidence: 99%
“…In addition, Metabolic Modulators Research Ltd, a University of Alberta spin-off company, was also involved in the testing of these new inhibitors. The authors and their respective affiliations have been disclosed in the author list.Correspondence to Dr Jason R. 15,19,20 This results in a continued low rate of glucose oxidation and a continued decrease in cardiac efficiency during the critical period of reperfusion.The primary reasons why fatty acid oxidation rates are high during and after ischemia are attributable to the fact that circulating plasma levels of fatty acids are dramatically elevated during and after ischemia 21 and that there are direct alterations in the subcellular control of fatty acid oxidation in the heart. One of these changes in fatty acid oxidation control is a dramatic decrease in malonyl CoA levels during and after ischemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation